The Impact of Virtual Reality (VR) and Augmented Reality (AR) on Graphic Design - Almomani, Islam Ghandi; Sultan Alkahteeb, Suhaib; Kamal Zoubi, Mohammad; Mohammad Issa, Mustafa; Atef Jaradat, Haytham (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The rapid advancements in Virtual Reality (VR) and Augmented Reality (AR) technologies are reshaping various industries, with graphic design being no exception. This paper explores the impact of VR and AR tools on graphic design, and the real-life applications from altering traditional design processes to enhancing creativity and visualization capabilities. We analyzed secondary sources, including academic journals, industry reports, and applications. This study explores the evolving landscape of graphic design in VR and AR technologies. The findings highlight the potential of these technologies to revolutionize design practices, education, and industry standards while offering a glimpse into the future of graphic design in a VR/AR-dominated era